Non-Hodgkinâs Lymphoma in Colon - Chowdhury, Monzorul Hasan; Chowdhury, Fasle Rabbi; Mohammed, Fazle Rabbi; Shams, Md Ziaus; Alam, Md Billal (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The incidence of Non-Hodgkin's lymphoma has steadily risen and while other cancers have increased 25%, NHL has increased >80%. In the majority of NHL patients, the disease arises in lymph nodes, but primary extranodal disease accounts for 30% of new lymphoma patients and often present as localized disease. We report a rare and interesting case of intermediate grade diffuse Non-Hodgkin's lymphoma in colon. A 30year old man presented to our department with the complaints of mild epigastric pain, occasional loose stools and, abdominal swelling for 3 months along with significant weight loss for the last 2 months. On examination, he appeared cachectic with only 33 kg, an intra-abdominal mass was palpable in the epigastrium rt side from the midline measuring 3cmx5cm, hard in consistency but does not move with respiration which was consisted with abdominal lymph node. USG guided FNAC of right upper abdominal mass revealed: Non-Hodgkin's lymphoma. Biopsy report of tissue from colon revealed diffuse non- Hodgkin's lymphoma, intermediate grade. To our knowledge, very few cases are reported so far with similar presentations and finally diagnosed with non-hodgkin's lymphoma of colon. Thus, in our clinical practice, if a middle aged person present with wt. loss, chronic diarrhoea, and abdominal swelling, we should also suspect this might be a case of Non-Hodgkin's lymphoma of colon as an extranodal presentation. DOI = 10.3329/jom.v8i2.1413 J MEDICINE 2007; 8 : 74-75